High variability of acetabular offset in primary hip osteoarthritis influences acetabular reaming: a computed tomography-based anatomic study - Merle, Christian; Innmann, Moritz Maximilian; Waldstein, Wenzel; Pegg, Elise C.; Aldinger, Peter; Gill, Harinderjit S.; Murray, David W.; Grammatopoulos, George (The journal of arthroplasty, 2019)
Background - The objectives of the present study were to (1) evaluate the accuracy and reliability of native acetabular offset (AO) measurements performed on conventional supine anterior-posterior (ap) pelvis radiographs with reference to computed tomography (CT) in patients with end-stage hip osteoarthritis (OA); (2) determine the minimum and maximum amount of medialization of the center of rotation (COR) simulating different reaming techniques; and (3) identify patients at increased risk of excessive medialization of the COR. - Methods - A consecutive series of corresponding 131 CT scans and radiographs of patients with primary hip OA was evaluated using validated software for three-dimensional acetabular and femoral measurements. We simulated the implantation of a hemispherical press-fit cup comparing anatomic and conventional reaming techniques and assessed corresponding changes in AO. - Results - Standardized ap pelvis radiographs allowed for an accurate and reliable assessment of AO compared with CT. Cup placement in the most lateral position (anatomic reaming technique) resulted in a mean implant-related medialization of 5.9 ± 3.4 mm. Anatomic cup placement did not require reaming to the true floor in 64 hips (49%). With the conventional reaming technique, the total medialization of the COR (implant-related and reaming-related) was 6.8 ± 2.9, with 34% of cases having a medialization ≥8 mm. - Conclusion - The present study highlights the variability of acetabular anatomy in patients with primary OA. AO can be accurately and reliably determined on conventional radiographs and appears to be independent of femoral shape and geometry. Depending on the preferred reaming technique a substantial number of patients appear at risk for excessive cup medialization.
Gesehen am 21.01.2020